Al-Kahfi di Malam Jum’at - Abdi Nafi Asshidiqi (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2023)
This article discusses reading al-Khafi letter at certain times. It also contains the introduction of Surah al-Kahfi among Muslims, reading models and how Muslims interpret the reading of Surah al-Kahfi. This model uses a descriptive analysis method by collecting data in the form of readings that are in accordance with the theme of the discussion. The results showed that most Muslims read Surat al-Kahfi when on Friday, because Friday is a very noble day for Muslims. However, there is also, who read on other days. The benefits of reading Surah Al-Kahf to get a reward from Allah, then as a form of self-protection from the slander of the Antichrist, and to find peaceand serenity.